2020
DOI: 10.1101/2020.02.25.964296
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Profiling of the reprogramome and quantification of fibroblast reprogramming to pluripotency

Abstract: Pluripotent state can be established via reprogramming of somatic nuclei by factors within an oocyte or by ectopic expression of a few transgenes. Considered as being extensive and intensive, the full complement of genes to be reprogrammed, however, has never been defined, nor has the degree of reprogramming been determined quantitatively. Here, we propose a new concept of reprogramome, which is defined as the full complement of genes that need to be reprogrammed to the expression levels found in pluripotent s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 34 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…We previously reported that genes involved in cellular morphogenesis have to be extensively and intensely reprogrammed for a successful conversion of human fibroblasts to iPSCs [13]. The current study reveals that these genes fall into three different categories.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…We previously reported that genes involved in cellular morphogenesis have to be extensively and intensely reprogrammed for a successful conversion of human fibroblasts to iPSCs [13]. The current study reveals that these genes fall into three different categories.…”
Section: Discussionmentioning
confidence: 72%
“…To answer these questions, this study took advantage of the novel concept of reprogramome we proposed recently [13]. This new concept allows one to define two sets of genes that need to be reprogrammed.…”
Section: Genes In Nucleic Acidmentioning
confidence: 99%
See 3 more Smart Citations